Ethanolic extract of Areca catechu seeds inhibit proliferation and induce apoptosis on MCF-7 cells - Meiyanto, Edy; Susidarti, Ratna Asmah; Handayani, Sri; Rahmi, Fitria (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2008)
Areca catechu seed contains antioxydant substances, supposed to have anticancer property. This research therefore addressed to examine the inhibitory effect of Areca catechu seed ethanolic extract (EP) on proliferating breast cancer cells, MCF-7. Areca catechu seed ethanolic extract (EP) standardization was done according to the standard of BPOM. Areca catechu seed powder extraction was done using ethanol 96%. Cytotoxic assay â to get the value of IC50 and to prevent the cell proliferation (using doubling time assay) â was carried out by using MTT assay. Apoptosis observation was done by acrydine orange- etidium bromide staining method (double staining). The result showed that treatment with Areca catechu seed ethanolic extract (25-100 Âµg/m) for 48 h caused 13-84% growth inhibition (IC 5077 Âµg/mL) of the cells, while arecoline (ARE) treatment (10-500 Âµg/mL) showed 8-73% inhibition (IC50 180 Âµg/mL). The extract also inhibited cell proliferation and induced apoptosis. These results conclude that Areca catechu seed ethanolic extract (EP) possesses antiproliferative effect through growth inhibition and apoptosis induction.Key words:MCF-7, Areca catechu, antiproliferativeÂ